Accommodating Multilingualism in Macedonia - Treneska-Deskoska, Renata (Social Inclusion, 2017)
The period since the independence of the Republic of Macedonia in 1991 has shown the political importance of language, as well as the political tensions that can arise over language-related issues. For a long time, multilingualism in Macedonia was a problem that threatened the unity and stability of the country. In 2001 the armed conflict in Macedonia showed that governmental policies of ignoring certain issues fueled ethnic divisions and facilitated a climate of insecurity. In order to terminate the armed conflict, Macedonia has since introduced constitutional changes relevant to linguistic diversity. The constitutional amendment regulating the official use of languages in Macedonia was as a result of a necessary compromise to terminate the armed conflict. The amendment is formulated in a vague and contradictory manner; full of loopholes, views provided on official languages leads to different interpretations and is still subject to disputes between experts, as well as party leaders in Macedonia. This vagueness led to politicians using the topic of the official use of languages as a talking point in every electoral campaign since 2001. This article will examine the challenges and possibilities that came from the constitutional amendment on the use of languages in Macedonia. It will also analyze the loopholes of the legal norms on the use of languages, and the problems of its implementation.